Decreased mannan-binding lectin level in adults with hypopituitarism; dependence on appropriate hormone replacement therapies - Matusiak, Aleksandra E.; Stępniak, Jan; Lewiński, Andrzej; Karbownik-Lewińska, Małgorzata (Frontiers in Immunology, 2023)
Background: Mannan-binding lectin (MBL) is a main component of the lectin pathway of the complement system. Although there are some studies showing links between endocrine and immune systems, the ones concerning hypopituitarism are limited. The aim of this study was to check whether there is any association between blood MBL level and pituitary hormone deficiencies and whether this relationship is affected by appropriate hormone replacement therapies. Methods: One hundred and twenty (120) inpatients, aged 18-92, were divided into two main groups, i.e. control individuals (21/120) and patients with pituitary diseases (99/120). The latter were diagnosed either with hypopituitarism (n=42) or with other pituitary diseases (not causing hypopituitarism) (n=57). Additionally, hypopituitary patients on appropriate replacement therapies (compensated hypopituitarism) were compared to patients on inappropriate replacement therapies (non-compensated hypopituitarism). Several parameters in blood serum were measured, including MBL level, pituitary and peripheral hormones and different biochemical parameters. Results: Serum MBL level was significantly lower in patients with hypopituitarism comparing to controls (1358.97±244.68 vs. 3199.30±508.46, p<0.001) and comparing to other pituitary diseases (1358.97±244.68 vs. 2388.12±294.99, p=0.015) and this association was confirmed by univariate regression analysis. We evaluated the distribution of patients with relation to MBL level; there was a clear difference in this distribution between control individuals (among whom no subjects had MBL level <500 ng/mL) and patients with hypopituitarism (among whom 43% of patients had MBL level <500 ng/mL). Moreover, patients with non-compensated hypopituitarism had lower mean and median MBL levels comparing to patients with compensated hypopituitarism (1055.38±245.73 vs. 2300.09±579.93, p=0.027; 488.51 vs. 1951.89, p=0.009, respectively) and this association was confirmed in univariate regression analysis. However, mean and median MBL levels in patients with compensated hypopituitarism vs. controls did not differ significantly (2300.09±579.93 vs. 3199.30±508.46, p=0.294; 1951.90 vs. 2329.16; p=0.301, respectively). Conclusion: Hypopituitarism in adults is associated with a decreased blood concentration of mannan-binding lectin, a phenomenon which does not exist in hypopituitary patients on the appropriate hormone replacement therapies. Therefore measurement of mannan-binding lectin level in patients with hypopituitarism may be considered as a parameter contributing to adjust optimal doses of hormone replacement therapies.